PERCEIVED IMPLICATION OF MANUAL FARMING ON THE LIVELIHOOD OF RURAL FARMERS IN ONDO STATE, NIGERIA - Idowu, T.C.; Olalekan, O.M.; Olley, B.O.; Alfred, S.D.Y. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the perceived implications of manual farming on the livelihood of rural farmers in Ondo State, Nigeria. A multi-stage random sampling technique was used to select 110 respondents from agrarian communities in Akure South and Akure North Local Government Areas. Data were collected using a well-structured questionnaire and analyzed using descriptive statistics, Chi-square, and Pearson Product Moment Correlation. The results revealed that the mean age, household size, farming experience and farm size of the respondents were 47.99 years, 6.47 persons, 13.11 years and 6.45 hectares. Majority (70%) of the farmers predominantly used manual farming methods. Key factors influencing this practice included the high cost of acquiring machinery (2.69), cultural factors (2.66), and lack of skills and access to mechanization (2.61). Farmers perceived manual farming as cost-effective for food provision on small plots but also recognized its implications, including being labor-intensive (4.40), leading to low productivity (4.19), and resulting in low income (4.00). The study concludes that manual farming is embraced for its cost-effectiveness, interventions such as subsidized mechanization, improved extension services, and targeted training are crucial to enhancing rural livelihoods and agricultural productivity.